2015
DOI: 10.15312/eurasianjvetsci.201518479
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a calf with jejunum intussusception: Case report

Abstract: Buzağıda jejenum invaginasyonunun operatif tedavisi: Olgu sunumu Öz Bu vaka sunumunda 5 aylık bir erkek buzağıda teşhis edilen jejunum invaginasyonunun klinik, laboratuar ve operasyon bulguları değerlendirildi. Tanımlanan klinik vakada hayvanın 3 gündür iştahsız olduğu ve defekasyon yapmadığı sahibinden öğrenildi. İç Hastalıkları kliniğinde yapılan klinik ve laboratuar muayenelerinden sonra hayvan cerrahi kliniğine sevk edildi. Sol açlık çukurluğundan laporatomi operasyonu yapıldı. Operasyonda bağırsaklar pato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, abdominal distension was not observed in 7 (23.33%) cases of the study. Similarly, abdominal distension was not observed in intussusception by (Karapinar and Kom, 2007;Erol et al, 2015;Khalphallah et al, 2016). Smith and Jones (2009) stated that rumen usually shows no obvious distention and may have less filling than normal, especially when the duration of the disease is prolonged.…”
Section: Abdominal Distensionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, abdominal distension was not observed in 7 (23.33%) cases of the study. Similarly, abdominal distension was not observed in intussusception by (Karapinar and Kom, 2007;Erol et al, 2015;Khalphallah et al, 2016). Smith and Jones (2009) stated that rumen usually shows no obvious distention and may have less filling than normal, especially when the duration of the disease is prolonged.…”
Section: Abdominal Distensionmentioning
confidence: 97%
“…Dharmaceelan et al, (2012) found equal percentage of pregnant and non-pregnant animals in their study on gastro-intestinal obstruction. Many authors have reported disease in calves (Horne, 1991;Constable et al, 1997;Erol et al, 2015). However, Sharma et al, (2003) reported a higher incidence of intestinal obstruction in pregnant animals.…”
Section: Pregnancy Statusmentioning
confidence: 99%